Polyester elastomer resin composition
The polyester elastomer resin composition addresses the challenge of achieving transparency and preventing bleed-out by using a specific combination of alkali metal salts and ethylene copolymers, resulting in a flexible and transparent material suitable for various applications.
Patent Information
- Application Number
- JP2020214551
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2040-12-24
AI Technical Summary
Existing polyester elastomer resin compositions struggle with achieving sufficient transparency while preventing bleed-out, which affects the appearance of molded products.
A polyester elastomer resin composition is developed, comprising 100 parts by weight of a polyester block copolymer, 0.01 to 3 parts by weight of an alkali metal salt of an aliphatic carboxylic acid with 10 to 15 carbon atoms, and 0.2 to 20 parts by weight of an ethylene copolymer with a metal carboxylic acid base on its side chains, optimizing the carbon number of aliphatic carboxylic acid metal salts to enhance transparency and prevent bleed-out.
The composition achieves excellent transparency with a haze value of 40% or less, while maintaining flexibility and preventing defective appearances due to bleed-out, making it suitable for applications requiring high transparency and durability.
Smart Images

Figure 0007650656000001 
Figure 0007650656000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester elastomer resin composition. [Background technology]
[0002] Polyester elastomers, which have crystalline aromatic polyester units such as polybutylene terephthalate units as hard segments and aliphatic polyether units such as poly(alkylene oxide) glycol as soft segments, not only have excellent extrusion and injection moldability, but also have high mechanical strength, rubber-like properties such as impact resistance, elastic recovery, flexural fatigue resistance, and flexibility, as well as excellent low- and high-temperature properties, water resistance, and chemical resistance. Furthermore, they are thermoplastic and easy to mold, so their applications are expanding to fields such as automobile parts, electrical and electronic parts, fibers, and films.
[0003] Although polyester elastomers are useful in this way, even though they are transparent when molten, they become cloudy and opaque when cooled and solidified, and therefore cannot be used in applications requiring translucency or transparency.
[0004] As a method for imparting transparency to polyester elastomers, a method of blending an alkali metal salt of an aliphatic carboxylate with a polyether polyester block copolymer is known (e.g., Patent Documents 1 and 2, etc.). However, in a system blended with a sodium salt of an aliphatic carboxylate, an excessive amount must be added to generate sufficient transparency, which results in many problems such as yellowing due to decomposition of the polyester main chain by the sodium salt and poor appearance of molded products due to bleeding out of the sodium salt of an aliphatic carboxylate.
[0005] Furthermore, a method has been proposed in which an ionomer resin, such as an alkali metal salt of an ethylene-methacrylic acid copolymer, is blended with a polyester elastomer (for example, Patent Documents 3 and 4). In this method, the molecular weight of the ionomer resin is large and it has good compatibility with polyester, so that it is possible to obtain a resin composition with little bleed-out and relatively high transparency. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 59-5142 [Patent Document 2] Japanese Patent Application Publication No. 6-306263 [Patent Document 3] Special Publication No. 58-24459 [Patent Document 4] Japanese Patent Application Publication No. 10-182954 Summary of the Invention [Problem to be solved by the invention]
[0007] However, although Patent Documents 3 and 4 do indeed show no bleeding on the surface of the molded article, they have many problems, such as the inability to obtain sufficient transparency to begin with, making it difficult to apply them to components that require high transparency.
[0008] An object of the present invention is to provide a polyester elastomer resin composition which not only exhibits excellent transparency but also suppresses the problem of poor appearance of molded products due to bleed-out and has excellent flexibility. [Means for solving the problem]
[0009] The present inventors focused on the carbon number of the aliphatic carboxylate metal salt. The aliphatic carboxylate metal salt with a small carbon number is preferable because it can improve transparency with a small amount of the metal salt, but the carbon chain is short, which causes bleed-out. On the other hand, the aliphatic carboxylate alkali metal salt with a large carbon number is preferable because it has a long carbon chain, suppresses bleed-out, inhibits the crystallinity of the polyether ester block copolymer, and improves transparency, but it is necessary to add a large amount to obtain sufficient transparency, and it was found that bleed-out still occurs. However, the present inventors thought that if the aliphatic carboxylate metal salt has an appropriate carbon number, it may be possible to improve transparency while suppressing bleed-out by combining it with other components.
[0010] As a result of intensive research into achieving the above object, the present inventors have come to propose the following invention. That is, the aspects of the present invention are as follows.
[0011] (1) A polyester elastomer resin composition comprising 100 parts by weight of a polyester block copolymer (A) having as its main components 10 to 50% by weight of a high melting point crystalline polymer segment (a) consisting of crystalline aromatic polyester units and 90 to 50% by weight of a low melting point polymer segment (b) consisting of aliphatic polyether units, 0.01 to 3 parts by weight of an alkali metal salt of an aliphatic carboxylic acid having 10 to 15 carbon atoms (B), and 0.2 to 20 parts by weight of an ethylene copolymer (C) having a carboxylate metal salt group in the side chain.
[0012] (2) The polyester elastomer resin composition according to (1), wherein the polyester elastomer resin composition has a haze value (cloudiness) of 40% or less as measured on a sheet having a thickness of 2 mm. Effect of the Invention
[0013] The present invention provides a polyester elastomer resin composition which not only exhibits excellent transparency but also has excellent flexibility and suppresses the problem of poor appearance of molded products due to bleed-out. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below.
[0015] The high melting point crystalline polymer segment (a) of the polyester block copolymer (A) used in the present invention is a polyester formed from an aromatic dicarboxylic acid or its ester-forming derivative and an aliphatic diol, and is preferably polybutylene terephthalate derived from terephthalic acid and / or dimethyl terephthalate and 1,4-butanediol. In addition, it is possible to use a dicarboxylic acid component such as isophthalic acid, phthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, diphenyl-4,4'-dicarboxylic acid, diphenoxyethanedicarboxylic acid, 5-sulfoisophthalic acid, or an ester-forming derivative thereof, and a diol having a molecular weight of 300 or less, for example, ethylene glycol, trimethylene glycol, pentamethylene glycol, hexamethanedicarboxylic acid, or the like. The polyester may be a polyester derived from an aliphatic diol such as ethylene glycol, neopentyl glycol, or decamethylene glycol, an alicyclic diol such as 1,4-cyclohexanedimethanol or tricyclodecanedimethylol, an aromatic diol such as xylylene glycol, bis(p-hydroxy)diphenyl, bis(p-hydroxyphenyl)propane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane, bis[4-(2-hydroxy)phenyl]sulfone, 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 4,4'-dihydroxy-p-terphenyl, or 4,4'-dihydroxy-p-quaterphenyl, or a copolymer polyester using two or more of these dicarboxylic acid components and diol components in combination. It is also possible to copolymerize a polyfunctional carboxylic acid component having three or more functionalities, a polyfunctional oxyacid component, and a polyfunctional hydroxy component in a range of 5 mol % or less.
[0016] The low melting point polymer segment (b) of the polyester block copolymer (A) used in the present invention is an aliphatic polyether and / or an aliphatic polyester. Examples of the aliphatic polyether include poly(ethylene oxide) glycol, poly(propylene oxide) glycol, poly(tetramethylene oxide) glycol, poly(hexamethylene oxide) glycol, copolymers of ethylene oxide and propylene oxide, ethylene oxide addition polymers of poly(propylene oxide) glycol, and copolymers of ethylene oxide and tetrahydrofuran. Examples of the aliphatic polyester include poly(ε-caprolactone), polyenantholactone, polycaprylolactone, polybutylene adipate, and polyethylene adipate. Among these aliphatic polyethers and / or aliphatic polyesters, poly(tetramethylene oxide) glycol, ethylene oxide addition products of poly(propylene oxide) glycol, poly(ε-caprolactone), polybutylene adipate, and polyethylene adipate are preferred in view of the elastic properties of the polyester block copolymers obtained. The number average molecular weight of these low melting point polymer segments is preferably about 300 to 6,000 in the copolymerized state.
[0017] In the polyester block copolymer (A) used in the present invention, the copolymerization amount of the high melting point crystalline polymer segment (a) is 10-50% by weight, and the copolymerization amount of the low melting point polymer segment (b) is 90-50% by weight. Preferably, in the polyester block copolymer (A), the copolymerization amount of the high melting point crystalline polymer segment (a) is 10-40% by weight, and the copolymerization amount of the low melting point polymer segment (b) is 90-60% by weight. More preferably, in the polyester block copolymer (A), the copolymerization amount of the high melting point crystalline polymer segment (a) is 10-30% by weight, and the copolymerization amount of the low melting point polymer segment (b) is 90-70% by weight. If the copolymerization amount of the high melting point crystalline polymer segment (a) is less than 10% by weight, the crystallinity becomes insufficient, and the moldability and heat resistance become poor. On the other hand, if the copolymerization amount of the high melting point crystalline polymer segment (a) exceeds 50% by weight, the transparency aimed at by the present invention is not fully expressed.
[0018] The polyester block copolymer (A) used in the present invention can be produced by a known method. For example, a method of transesterifying a lower alcohol diester of a dicarboxylic acid, an excess amount of a low molecular weight glycol, and a low melting point polymer segment component in the presence of a catalyst, and polycondensing the resulting reaction product. Alternatively, a method of esterifying a dicarboxylic acid, an excess amount of a glycol, and a low melting point polymer segment component in the presence of a catalyst, and polycondensing the resulting reaction product. Alternatively, a method of randomizing a high melting point crystalline segment by adding a low melting point segment component to the high melting point crystalline segment through a transesterification reaction. A method of connecting a high melting point crystalline segment and a low melting point polymer segment with a chain linking agent. Furthermore, when poly(ε-caprolactone) is used for the low melting point polymer segment, any method may be used, such as an addition reaction of ε-caprolactone monomer to the high melting point crystalline segment.
[0019] The alkali metal salt of an aliphatic carboxylic acid (B), which is one of the components used in the resin composition of the present invention, is used as a clarifying agent that has the effect of making the polyester elastomer resin composition transparent. The alkali metal salt of an aliphatic carboxylic acid (B) of the present invention has a carbon number of 10 to 15. It preferably has a carbon number of 10 to 14, and more preferably has a carbon number of 10 to 13. The aliphatic carboxylic acid is a compound in which a carboxyl group is attached to a linear or branched aliphatic group, and may have other substituents such as an unsaturated group, an alicyclic group, an aromatic group, a hydroxyl group, or a phosphate ester group in a part of the bond. Examples of the aliphatic carboxylic acid include capric acid (carbon number 10), undecylic acid (carbon number 11), lauric acid (carbon number 12), tridecylic acid (carbon number 13), myristic acid (carbon number 14), and pentadecylic acid (carbon number 15), among which capric acid, lauric acid, and myristic acid are preferred. Among the alkali metal salts, sodium salts are preferred in terms of solubility in polyester elastomers and good crystal nucleation properties.
[0020] The aliphatic carboxylic acid alkali metal salt (B) of the present invention is an aliphatic carboxylic acid alkali metal salt having 10 to 15 carbon atoms from the viewpoints of melting property, compatibility with polyether ester block copolymer, and bleed-out. An aliphatic carboxylic acid alkali metal salt having 9 or less carbon atoms is preferable because it can improve transparency with a small amount of the compound, but it causes bleed-out because of its short carbon chain. On the other hand, an aliphatic carboxylic acid alkali metal salt having 16 or more carbon atoms is preferable because it suppresses bleed-out because of its long carbon chain and inhibits the crystallinity of the polyether ester block copolymer to improve transparency, but a large amount must be added to obtain sufficient transparency, and adding a large amount causes bleed-out.
[0021] The amount of the aliphatic carboxylic acid alkali metal salt (B) is 0.01 to 3 parts by weight, preferably 0.05 to 2 parts by weight, more preferably 0.1 to 1 part by weight.
[0022] If the amount of the alkali metal salt of an aliphatic carboxylic acid having 10 to 15 carbon atoms (B) is less than 0.01 parts by weight, sufficient light transmission and transparency cannot be obtained, and if it exceeds 3 parts by weight, a large amount of gas is generated during processing, which affects moldability. As a result, mold transferability becomes poor, the molded product surface cannot be produced cleanly, and the haze value deteriorates.
[0023] The ethylene copolymer (C) having a metal carboxylate group in the side chain, which is one of the components used in the resin composition of the present invention, is a copolymer of ethylene and an ethylenically unsaturated carboxylic acid such as acrylic acid, methacrylic acid, maleic acid, or fumaric acid, neutralized with an alkali metal ion, an alkaline earth metal ion, or a zinc ion, and is commercially available, for example, as "Surlyn" from DuPont or "Himilan" from Dow Mitsui Polychemicals. Of these, those neutralized with an alkali metal ion such as sodium, potassium, or lithium are preferred.
[0024] The ethylene copolymer (C) having a metal carboxylate salt group in the side chain of the present invention is blended in an amount of 0.2 parts by weight or more and less than 20 parts by weight, preferably 0.5 to 15 parts by weight, particularly preferably 1 to 10 parts by weight.
[0025] When the amount of the ethylene copolymer (C) having a carboxylate metal salt in the side chain is less than 0.2 parts by weight, the light transmission and transparency are insufficient, and when it is 20 parts by weight or more, phase separation occurs, and the mechanical properties, light transmission and transparency are reduced. It is important to use a specific amount of an aliphatic carboxylate alkali metal salt (B) and a specific amount of an ethylene copolymer (C) having a carboxylate metal salt in the side chain, because it can suppress gas generation during processing and improve releasability.
[0026] The resin composition of the present invention preferably has a haze value (cloudiness) of 40% or less, measured on a sheet having a thickness of about 2 mm. A sheet with a haze value of less than 40% is transparent to the naked eye, and when the sheet is placed on a printed matter, the characters are very clearly visible. A sheet with a haze value (cloudiness) of 40% or less can meet the transparency requirements for applications such as automobile parts and electronic and electrical applications.
[0027] Furthermore, when the resin composition of the present invention is required to have high-temperature long-term durability, it is preferable to add an antioxidant. Examples of the antioxidant include hindered phenols such as 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 1,1,3-tri(4-hydroxy-2-methyl-5-t-butylphenyl)butane, 1,1-bis(3-t-butyl-6-methyl-4-hydroxyphenyl)butane, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-benzenepropanoic acid, pentaerythritol tetrakis(3,5-di-t-butyl ...1,1-bis(3-t-butyl-6-methyl-4-hydroxyphenyl)isocyanurate, 1,1-bis(3-t-butyl-6-methyl-4-hydroxyphenyl)isocyanurate, 1,1-bis(3-t-butyl-6-methyl-4-hydroxyphenyl)isocyanurate, 1,1-bis(3-t-butyl-6-methyl-4-hydroxyphenyl)isocyanurate, 1,1-bis(3-t-butyl-6-methyl-4-hydroxyphenyl)isocyanurate, 1,1-bis(3-t-butyl-6-methyl-4-hydroxyphenyl)isocyanurate, 1,1-bis( t-butyl-4-hydroxyphenyl)propionate, and the like. Phosphorus-based compounds include 3,9-bis(p-nonylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, tri(mononylphenyl)phosphite, triphenoxyphosphine, and isodecylphosphite. These compounds can be used alone or in combination. The amount of the compound added is preferably 0.1% or more and 5% or less based on the mass of the resin composition. If the amount is less than 0.1%, the effect of preventing thermal deterioration may be poor. If the amount exceeds 5%, the color tone of the resin may be adversely affected.
[0028] Furthermore, when weather resistance is required for the resin composition of the present invention, it is preferable to add an ultraviolet absorber and / or a hindered amine compound. For example, examples of benzophenone-based, benzotriazole-based, triazole-based, nickel-based, and salicylic light stabilizers that can be blended with the polyester thermoplastic elastomer used in the present invention include 2,2'-dihydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octoxybenzophenone, pt-butylphenyl salicylate, 2,4-di-t-butylphenyl-3,5-di-t-butyl-4-hydroxybenzoate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-amyl-phenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α-dimethylbenzylphenyl)benzotriazole, 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzazotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzothiazole, 2,5-bis-[5'-t-butylbenzoxazolyl-(2)]-thiophene, bis(3,5-di-t-bu ethyl-4-hydroxybenzyl phosphate monoethyl ester) nickel salt, 2-ethoxy-5-t-butyl-2'-ethyl oxalic acid bis-anilide 85-90% and 2-ethoxy-5-t-butyl-2'-ethyl-4'-t-butyl oxalic acid bis-anilide 10-15% mixture, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 2-ethoxy-2'-ethyl oxalic acid bis-anilide, 2-[2'-hydroxy-5 Examples of light stabilizers include 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, 2-hydroxy-4-i-octoxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, 2-hydroxy-4-octadecyloxybenzophenone, and phenyl salicylate.The amount of addition is preferably 0.1% or more and 5% or less based on the mass of the resin composition.
[0029] The resin composition of the present invention may contain various other additives, such as resins other than those of the present invention, inorganic fillers, stabilizers, and antioxidants that are widely used as additives to thermoplastic elastomers, within the scope of the present invention without impairing the characteristics of the present invention.
[0030] Other additives may also be added, such as color pigments, inorganic or organic fillers, coupling agents, tackiness improvers, quenchers, stabilizers such as metal deactivators, and polyfunctional glycidyl group-containing styrene-based polymers. The resin composition of the present invention preferably contains the polyether ester block copolymer (A), the aliphatic carboxylic acid alkali metal salt (B) having 10 to 15 carbon atoms, and the ethylene-based copolymer (C) having a carboxylate metal salt in the side chain in a total amount of 80% by mass or more. The total amount of (A) and (B), or (A), (B), and (C) is more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0031] The method for producing the resin composition of the present invention is not particularly limited, and examples of the method that can be used as appropriate include a method in which a raw material containing a polyester block copolymer, an alkali metal salt of an aliphatic carboxylate having 15 to 20 carbon atoms, an ethylene-based copolymer having a carboxylate metal salt in its side chain, and other additives is fed to a screw-type extruder and melt-kneaded together, or a method in which the polyester block copolymer is first fed to a screw-type extruder and melted, and then the alkali metal salt of an aliphatic carboxylate having 15 to 20 carbon atoms, the ethylene-based copolymer having a carboxylate metal salt in its side chain, and other additives are fed to the screw-type extruder from another feed port and kneaded.
[0032] The resin composition of the present invention can be molded by a conventional melt molding method, such as injection molding or extrusion molding, for use in various applications, including as fibers, films, sheets, tubes, etc. EXAMPLES
[0033] The effects of the present invention will be described below with reference to examples. In the examples, % and parts are all by weight unless otherwise specified. The physical properties shown in the examples were measured as follows.
[0034] Melting point Using a differential scanning calorimeter (DSC-910 manufactured by Du Pont), the top temperature of the melting peak was measured when the sample was heated at a temperature increase rate of 10° C. / min in a nitrogen gas atmosphere.
[0035] Surface hardness (Shore D scale) Measured according to ASTM K-7215.
[0036] Haze value Using an electric injection molding machine (NEX-1000) manufactured by Nissei Plastics Industrial Co., Ltd., a test piece of 125 mm x 75 mm with a thickness of 2 mm was produced at 220°C (mold temperature: 40°C). The surface roughness of the test piece was measured using a VK-9700 manufactured by KEYENCE Corporation and found to be 0.46 μm. The test piece was used to measure the surface roughness using a DIRECT READING HAZEMETER manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with ASTM D1003.
[0037] Bleed out The test pieces, 2 mm thick and 125 mm x 75 mm, prepared under the conditions described above were heat-treated in a thermostatic chamber at 80°C for three weeks, and then removed and visually inspected for the state of precipitation on the surface.
[0038] Reference example Production of polyester block copolymer (A-1) 270 parts of terephthalic acid, which is a high melting point crystalline polymer segment made of crystalline aromatic polyester, 686 parts of poly(tetramethylene oxide) glycol (PTMG-1400) with a number average molecular weight of about 1400, which is a low melting point polymer segment made of aliphatic polyether units, 311 parts of 1,4-butanediol (1,4-BD), and 1.8 parts of titanium tetrabutoxide were charged together in a reaction vessel equipped with a helical ribbon type stirring blade, and the mixture was heated at 190 to 225°C for 3 hours to perform an esterification reaction while distilling the reaction water out of the system. After adding 0.5 parts of "Irganox" 1098 (a hindered phenol-based antioxidant manufactured by Ciba-Geigy), the reaction mixture was heated to 245°C, and then the pressure in the system was reduced to 0.2 mmHg over 50 minutes, and polymerization was performed under those conditions for 2 hours and 45 minutes. The obtained polymer was discharged in the form of a strand into water and cut into pellets.
[0039] Production of polyester block copolymer (A-2) 348 parts of terephthalic acid, which is a high melting point crystalline polymer segment made of crystalline aromatic polyester, 645 parts of poly(tetramethylene oxide) glycol (PTMG-1400) with a number average molecular weight of about 1400, which is a low melting point polymer segment made of aliphatic polyether units, 340 parts of 1,4-butanediol (1,4-BD), and 0.2 parts of titanium tetrabutoxide were charged into a reaction vessel equipped with a helical ribbon type stirring blade, and the mixture was heated at 190 to 225°C for 3 hours to perform an esterification reaction while distilling the reaction water out of the system. After adding 0.5 parts of "Irganox" 1098 (a hindered phenol-based antioxidant manufactured by Ciba-Geigy), the reaction mixture was heated to 245°C, and then the pressure in the system was reduced to 0.2 mmHg over 50 minutes, and polymerization was performed under those conditions for 2 hours and 45 minutes. The obtained polymer was discharged into water in the form of a strand, and cut into pellets.
[0040] Production of polyester block copolymer (A-3) 234 parts of terephthalic acid, which is a high melting point crystalline polymer segment made of crystalline aromatic polyester, 754 parts of poly(tetramethylene oxide) glycol (PTMG-2000) with a number average molecular weight of about 2000, which is a low melting point polymer segment made of aliphatic polyether units, 228 parts of 1,4-butanediol (1,4-BD), and 0.2 parts of titanium tetrabutoxide were charged into a reaction vessel equipped with a helical ribbon type stirring blade, and the mixture was heated at 190 to 225 ° C for 3 hours to perform an esterification reaction while distilling the reaction water out of the system. After adding 0.5 parts of "Irganox" 1330 (a hindered phenol-based antioxidant manufactured by Ciba-Geigy), the reaction mixture was heated to 245 ° C, and then the pressure in the system was reduced to 0.2 mmHg over 50 minutes, and polymerization was performed under those conditions for 3 hours and 30 minutes. The obtained polymer was discharged into water in the form of a strand, and cut into pellets.
[0041] Table 1 shows the compositions and physical properties of A-1, A-2, and A-3.
[0042] [Table 1]
[0043] Examples 1 to 5 The polyester block copolymer (A-1), (A-2) or (A-3) obtained in the reference examples was dry-blended with sodium laurate (B-1) and an ethylene copolymer having a sodium carboxylate group in the side chain ("Surlyn" AD8610 manufactured by Du Pont) (C-1) or ("Himilan" 1707 manufactured by Mitsui Dow Polychemical Co., Ltd.) (C-2) in the mixing ratios shown in Table 2, melt-kneaded using a twin-screw extruder having a cylinder diameter of 45 mmφ, and then pelletized. The pellets were dried at 80°C for 3 hours, and then a test piece of 125 mm x 75 mm with a thickness of 2 mm was prepared at 220°C (mold temperature: 40°C) using an electric injection molding machine (NEX-1000) manufactured by Nissei Plastic Industrial Co., Ltd. The haze value was measured using the obtained 2 mm thick sheet, and the presence or absence of bleed-out was examined. The surface hardness was also measured. The results are shown in Table 2.
[0044] Comparative Examples 1 to 5 The polyester block copolymer (A-1), (A-2), or (A-3) obtained in the Reference Examples was dry-blended with sodium laurate (B-1) having 12 carbon atoms, sodium stearate (B-2) having 17 carbon atoms, or sodium caprylate (B-3) having 8 carbon atoms in the blending ratios shown in Table 2, and melt-kneaded, pelletized, and injection-molded in the same manner as in Examples 1 to 5. The haze value was measured using the obtained 2 mm-thick sheet, and the presence or absence of bleed-out was also examined. The surface hardness was also measured. The results are shown in Table 2.
[0045] [Table 2]
[0046] As is clear from Table 2, a resin composition in which an alkali metal salt of an aliphatic carboxylic acid having 10 to 15 carbon atoms is blended within the range of the present invention to a polyester block copolymer having a low melting point crystalline polymer segment of 90 to 50% by weight is excellent in transparency. When an aliphatic carboxylic acid having 16 or more carbon atoms is blended, the transparency is insufficient, and adding a large amount to improve the transparency causes bleed-out. On the other hand, when an aliphatic carboxylic acid having 9 or less carbon atoms is blended, the transparency is excellent, but bleed-out occurs. [Industrial Applicability]
[0047] The resin composition of the present invention has higher transparency than conventional polyester elastomer resin compositions. Not only is it excellent in terms of adhesion, but it also has excellent bleeding prevention properties on the surface of molded products, making them flexible and transparent. It is useful as a molding material for desired molded articles.
Claims
1. A polyester elastomer resin composition comprising 100 parts by weight of a polyester block copolymer (A) having as main components 10 to 50% by weight of a high melting point crystalline polymer segment (a) composed of a crystalline aromatic polyester unit and 90 to 50% by weight of a low melting point polymer segment (b) composed of an aliphatic polyether unit, 0.1 to 1 part by weight of an alkali metal salt of an aliphatic carboxylic acid having from 10 to 15 carbon atoms (B), and 0.2 to 20 parts by weight of an ethylene copolymer (C) having a carboxylate metal salt group in a side chain.
2. 2. The polyester elastomer resin composition according to claim 1, which has a haze value (cloudiness) of 40% or less as measured on a sheet having a thickness of 2 mm.
Citation Information
Patent Citations
Thermal label printer
JP1983024459A
Preparation of fatty acid lower alkyl ester
JP1984005142A
Production of polyester-ester block copolymer and molded article thereof
JP1994306263A
Transparent polyester elastomer composition
JP1996311317A
Polyester elastomer resin composition
JP1998182954A